2020
DOI: 10.1177/1753193420932477
|View full text |Cite
|
Sign up to set email alerts
|

DendroPrime as an adhesion barrier on fracture fixation plates: an experimental study in rabbits

Abstract: We tested the anti-adhesional effect of a new thiol-ene-based coating in a rabbit model. In 12 New Zealand white rabbits, the periosteum and cortex of the proximal phalanx of the second toe of both hind paws was scratched. Stainless steel plates were fixated with screws. One plate was coated with DendroPrime and the other left bare. The non-operated second toes of both hind paws of an additional four rabbits served as controls. Seven weeks after surgery, the soft tissue adhesion to the plates was evaluated mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The high monomer conversion avoids the issue of monomer leach out present in commonly used methacrylate dental composites. [ 18,19 ] In vivo studies in rabbits [ 20 ] and rats [ 17 ] have also demonstrated the resistance of the TEC composite to soft‐tissue adhesions.…”
Section: Introductionmentioning
confidence: 99%
“…The high monomer conversion avoids the issue of monomer leach out present in commonly used methacrylate dental composites. [ 18,19 ] In vivo studies in rabbits [ 20 ] and rats [ 17 ] have also demonstrated the resistance of the TEC composite to soft‐tissue adhesions.…”
Section: Introductionmentioning
confidence: 99%
“…An excellent biological profile is essential for any material destined for biomedical applications. In the case of the TATO thermoset and composite systems, extensive studies have been previously performed including comprehensive safety evaluations and preclinical trials 13,15,16 . These studies have shown that the TATO systems display no cytotoxicity, genotoxicity, skin irritation or inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of the TATO thermoset and composite systems, extensive studies have been previously performed including comprehensive safety evaluations and preclinical trials. 13,15,16 These studies have shown that the TATO systems display no cytotoxicity, genotoxicity, skin irritation or inflammation. The cytotoxicity of the 3D printed TATO systems (thermosets 4, 5, and the composite) were evaluated against human dermal fibroblasts (hDF) and mouse monocytes (Raw 264.7) to determine if the addition of PETMP, Sudan I, PYG or the combination of mHA and nHA had any impact on the biological profile of the TATO systems.…”
Section: Cytotoxicity Of 3d Printed Tec Systemsmentioning
confidence: 99%
See 2 more Smart Citations